The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0168252
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Consequences of a Break in S1P1-Dependent Homeostasis of Vascular Permeability Revealed by S1P1 Competitive Antagonism

Abstract: RationalHomeostasis of vascular barriers depends upon sphingosine 1-phosphate (S1P) signaling via the S1P1 receptor. Accordingly, S1P1 competitive antagonism is known to reduce vascular barrier integrity with still unclear pathophysiological consequences. This was explored in the present study using NIBR-0213, a potent and selective S1P1 competitive antagonist.ResultsNIBR-0213 was tolerated at the efficacious oral dose of 30 mg/kg BID in the rat adjuvant-induced arthritis (AiA) model, with no sign of labored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
15
2
Order By: Relevance
“…Because of their ability to induce lymphopenia, S1P 1 antagonists have been studied in mouse models of inflammatory arthritis [45], and while blocking autoreactive T cells from entering target tissues is beneficial for reducing inflammation and organ damage, the effects on ECs may be deleterious. Indeed, prolonged treatment of mice with the S1P 1 antagonist NIBR-0213 to treat adjuvant-induced arthritis decreased joint inflammation, but long term administration resulted in pulmonary edema, perivascular fibrosis, and functional lung impairment [46]. Because patients with SLE and RA frequently have lung involvement, they may be more vulnerable to pulmonary vascular leak and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their ability to induce lymphopenia, S1P 1 antagonists have been studied in mouse models of inflammatory arthritis [45], and while blocking autoreactive T cells from entering target tissues is beneficial for reducing inflammation and organ damage, the effects on ECs may be deleterious. Indeed, prolonged treatment of mice with the S1P 1 antagonist NIBR-0213 to treat adjuvant-induced arthritis decreased joint inflammation, but long term administration resulted in pulmonary edema, perivascular fibrosis, and functional lung impairment [46]. Because patients with SLE and RA frequently have lung involvement, they may be more vulnerable to pulmonary vascular leak and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that endotoxin-induced microvascular permeability and inflammation leading to acute lung and kidney injury in mice can be reduced by direct application of either S1P or fingolimod (Peng et al, 2004). On the contrary, application of a S1P 1 receptor antagonist (W146), induced loss of capillary integrity in mouse skin and lung (Sanna et al, 2006), and the most recently developed potent S1P 1 selective antagonist NIBR-0213 induced transient lung and heart permeability defects in rats, which promoted chronic inflammatory remodeling (Bigaud et al, 2016). Furthermore, a conditional gene deletion approach was used to demonstrate that plasma S1P is crucial for vascular integrity.…”
Section: Specific Fingolimod Targetsmentioning
confidence: 99%
“…A previous report 34 by using mice renal IRI models demonstrated that mice treated with a specific S1PR1 antagonist (W146) showed exacerbated renal and hepatic injury after renal IRI. In addition, another previous report 35 revealed that NIBR-0213, another selective S1PR1 antagonist, induced dose-dependent acute vascular pulmonary leakage and pleural effusion in rat models. Based on these studies, we speculate that the selective S1PR1 antagonism at least does not have hepatoprotective effect in hepatic IRI even if the type of animal models is different.…”
Section: Discussionmentioning
confidence: 78%